(3hSjdI GdabjQ GdeMJGL Edi TaGYI UGMH GddhGA hGdJGLs - (3GdMSf Hf GdTQja Hf GdegOj Hf CMeO Hf GdjRjO GdYdhj GdecfGSj,J (B1333 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dgPG heG cfG dfgJOi dhdG Cf gOGfG Gddg hHYO, aEf CRci eGJYWQ GdeLGdS Hg HK NUGFU SjO SGOGJ GdCfHjGA s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JNQjLg Ydi jO ebjOg GdMSf Hf GdjRjO GdYdhi GdecfGSj GdSdLeGSj YGe (B1337 s
(3Vef eLehY , JQJjHgG (B: (3ef U (B292 - (3U(B399s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B469 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(637 (3c(B) s
Keywords: (3GdJGQjNs